Virus Bioinformatics - Robertson, David (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Virus bioinformatics is evolving and succeeding as an area of research in its own right, representing the interface of virology and computer science. Bioinformatic approaches to investigate viral infections and outbreaks have become central to virology research, and have been successfully used to detect, control, and treat infections of humans and animals. As part of the Third Annual Meeting of the European Virus Bioinformatics Center (EVBC), we have published this Special Issue on Virus Bioinformatics.